Internal Versus Edge Row Comparison in Jajar Legowo 4:1 Rice Planting Pattern at Different Frequency of Fertilizer Applications - Kartika, Kartika; Lakitan, Benyamin; Sanjaya, Nanda; Wijaya, Andi; Kadir, Sabaruddin; Kurnianingsih, Astuti; Widuri, Laily Ilman; Siaga, Erna; Meihana, Mei (AGRIVITA, Journal of Agricultural Science, 2018)
Jajar legowo 4:1 cropping pattern has been adopted by rice farmers; however, there has been limited information on the comparison between internal and edge rows. In addition, the effects of timing and frequency of fertilizer applications on rice cultivated at riparian wetland also have to be understood. In this research, both single and split applications of fertilizer were employed. The single fertilizer applications were applied at 15 days after transplanting (DAT) (T1), 30 DAT (T2), 45 DAT (T3); and the split applications were 15+30 DAT (T4), 15+45 DAT (T5), 30+45 DAT (T6), and 15+30+45 DAT (T7). Results of this research indicated that crops in the edge rows produced higher leaf area index but those at internal rows produced higher dry weight biomass. Split fertilizer application to three times (T7) increased the weight of grains and number of filled spikelet but did not affect other shoot and root growth traits. Overall, fertilizer application increased leaf chlorophyll and nitrogen content. Jajar legowo 4:1 planting pattern and split fertilizer application to three times are recommended for increasing yield in rice cultivated at riparian wetlands.